2013
DOI: 10.1017/jsc.2013.29
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Attitudes and Practices of Shisha Smoking Among Medical Practitioners in Karachi, Pakistan

Abstract: Background: It is well established that tobacco use in the form of shisha has adverse effects similar to cigarette smoking. Medical-practitioners can play an important role in spreading awareness regarding health hazards associated with shisha smoking. Misconception about shisha is an important factor responsible for its increasing use, the need to evaluate medical practitioner's knowledge about shisha is an important step in controlling the growing epidemic.Objectives: To investigate the knowledge, attitudes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Similarly, in other studies only a minority of students had any intent to stop shisha smoking [24,30]. Even among shisha-using medical practitioners, the majority was not ready to quit [29].…”
Section: Knowledge Attitude and Practicesmentioning
confidence: 73%
See 1 more Smart Citation
“…Similarly, in other studies only a minority of students had any intent to stop shisha smoking [24,30]. Even among shisha-using medical practitioners, the majority was not ready to quit [29].…”
Section: Knowledge Attitude and Practicesmentioning
confidence: 73%
“…In Pakistani adolescents aged 13-17 years the rate of shisha smoking was 39% [28]. In a study involving medical practitioners in Pakistan, 29.5% admitted to shisha smoking at some point in their lives [29]. A cross-sectional descriptive study executed in four cities of Pakistan including Karachi, Islamabad, Rawalpindi and Peshawar at shisha cafes, shopping malls and restaurants found a higher prevalence of 61% [30].…”
Section: R E S U L T S and Discussion Prevalencementioning
confidence: 99%
“…In a study conducted by Moyer VJP et al, health care professionals were found to be helping adolescents to change their behavior [71] using evidence-based counseling tools [62]. Similarly, Kumar et al reported that the lack of WPS control programs among health care professionals can act as a positive vision to WP and cause low incentive to cooperate in WPS control programs [72][73].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Moyer VJP (2013), health care professionals were found to be helping adolescents to change their behavior [78]. On the other hand, reported that the prevalence of WPS among health care professionals, especially medical and nursing students [79], can act as a positive vision to WP and cause low motivation to cooperate in WPS control programs [80,81].…”
Section: Control Interventionsmentioning
confidence: 99%